FEATURES OF DETERMINING THE COST OF TRANSPORT SERVICES - Zhumatayeva G.; Nurgalieva M.; Baiburaeva Zh.; Musabyaev B.; Zhanbirov Zh.; Taran I. (Academic Journal of Physical and Chemical Sciences, 2020)
The strong competition in the logistics market enforces the service provider companies to enhance the capabilities of their management accounting systems. It is of high importance to know the real costs of transport services as well as the cost efficiency of activities contributing to the production of services. This information is needed for assessing the profitability and operation efficiency and for determining the price of services. Traditional costing methods, however, are not always able to provide the information necessary for decision support in the required quality. They may even distort service cost calculations as detailed cost driver analyses are not applied within conventional costing regimes. Thus it is worth introducing alternative cost calculation methods which improve the accuracy and reliability of service cost data [1]. To properly manage costs in transport logistics, it is necessary to optimize all stages of the transport and logistics process-from choosing the type of transport and building the supply chain to planning routes and monitoring the execution of tasks. The article deals with determining the optimal cost of auto cargo transportation, taking into account internal and external factors of influence. The results of the research in the article show that a transport company should have different payment options for paying for a completed flight with specific brands of cars, i.e. the cost of one m3 , t, km, depending on the type of orders and the distance of transportation. The materials consider the methodology of determining the contractual price of transport services in the Republic of Kazakhstan. In the market conditions, the main objective is the correctness and accuracy of the assessment of the actual costs of the implementation of the transport service and, as a result, the correct pricing of this service.